2017
DOI: 10.7150/thno.17252
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent Effects of Gold Nanoparticles on Osteogenic Differentiation of Human Periodontal Ligament Progenitor Cells

Abstract: Gold nanoparticles (AuNPs) have been reported to promote osteogenic differentiation of mesenchymal stem cells and osteoblasts, but little is known about their effects on human periodontal ligament progenitor cells (PDLPs). In this study, we evaluated the effects of AuNPs with various diameters (5, 13 and 45 nm) on the osteogenic differentiation of PDLPs and explored the underlying mechanisms. 5 nm AuNPs reduced the alkaline phosphatase activity, mineralized nodule formation and expression of osteogenic genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 48 publications
5
77
0
1
Order By: Relevance
“…Furthermore, autophagy inhibitors could reverse the up‐regulation of osteogenesis. These results suggested that autophagy might be involved in the osteogenic differentiation of PDLPs and influenced further on the regeneration of periodontal tissues (Zhang, Kong, Zhang, Yang, & Fan, ). The other researchers examined the function of autophagy in osteoblasts and found a negative relation between autophagy and apoptosis.…”
Section: Autophagy and Periodontal Regeneration And Reconstructionmentioning
confidence: 98%
“…Furthermore, autophagy inhibitors could reverse the up‐regulation of osteogenesis. These results suggested that autophagy might be involved in the osteogenic differentiation of PDLPs and influenced further on the regeneration of periodontal tissues (Zhang, Kong, Zhang, Yang, & Fan, ). The other researchers examined the function of autophagy in osteoblasts and found a negative relation between autophagy and apoptosis.…”
Section: Autophagy and Periodontal Regeneration And Reconstructionmentioning
confidence: 98%
“…Moreover, compared to 13-nm-sized GNPs, 5 nm-sized GNPs were shown to be more toxic to hypoxic human renal proximal tubular cells (HK-2), as indicated by increased apoptosis and autophagic cell death [ 104 ]. On the contrary, 13 and 45 nm-sized GNPs were reported to induce autophagy in human periodontal ligament progenitor cells at 10 μM, but 5 nm-sized GNPs did not [ 105 ]. Considering the GNPs used in these two studies were synthesized via a similar NaBH 4 reduction method, the surfaces of these GNPs were alike.…”
Section: Gnp-induced Autophagymentioning
confidence: 99%
“…For the FTIR measurements, small pieces of nanobre, gelatin and 3D material were tested by using a thermo nicolet FT-IR (Nexus, USA). 4,17,18 Briey, periodontium was gently scraped from the one-third of the root surface and then digested in a solution of collagenase type I (3 mg mL À1 ) and dispase (4 mg mL À1 ) for 1 h at 37 C. The single-cell suspensions were plated into a T25 culture ask and incubated in an alphaminimum essential medium (a-MEM; Gibco, USA) supplemented with 20% (vol/vol) foetal bovine serum (FBS; Gibco, USA) and 2% (vol/vol) penicillin/streptomycin (P/S; Gibco, USA) at 37 C in a humidied CO 2 incubator. Cells at passage P3 to P5 were used for the following study.…”
Section: Methodsmentioning
confidence: 99%